ENVIRONMENTAL ASSESSMENT OF RIPARIAN FORESTS IN THE ALTO MEIA PONTE WATERSHED – GO, BRAZIL - de Oliveira, Pedro Luiz Teodoro Clemente; Griebeler, Nori Paulo; Ramos, João Ricardo Nobre (Seven Editora, 2026)
Monitoring vegetation degradation in the surroundings of water sources is essential to assess environmental impacts and to support actions aimed at restoring ecological balance between riparian forests and watercourses. In this context, the proposed study is justified by integrating geoprocessing and remote sensing tools into environmental analysis. This study aimed to evaluate the presence and condition of remnant vegetation within the Permanent Preservation Areas (PPAs) of the Meia Ponte River Basin upstream of the Raw Water Pumping Station operated by SANEAGO in Goiânia, Goiás. The assessment procedures involved the use of QuantumGIS (QGIS) software to delineate the watershed based on the Digital Elevation Model (DEM) from the TOPODATA project. Publicly available satellite imagery from Landsat 8–9 and Sentinel-2 was also used, along with the application of the Normalized Difference Vegetation Index (NDVI) and pixel reclassification to identify Cerrado phytophysiognomies that include riparian vegetation. The results revealed differences in sensor accuracy, with Sentinel-2 presenting higher spatial accuracy. They also indicated that only 3.62% and 5.09% of the total basin area (Landsat 8–9 and Sentinel-2, respectively) corresponds to remnant vegetation within PPAs, highlighting significant pressure on riparian forests associated with water sources. The study demonstrated the relevance of geotechnologies as effective tools for assessing PPAs in the watershed under analysis. Satellite image analysis enabled accurate mapping of river tributaries and identification of the presence and absence of vegetation adjacent to water sources within legally protected buffer zones. DOI: https://doi.org/10.56238/sevened2026.008-072